Genetics Of Hearing Loss: Focusing On Gene Therapy - Ziske Maritska; Fitri Az-Zahrah; Amalia Salsabilla; Rahmat Afif; Setiadi Winata; Robby Pardiansyah; Ayu Purnama Sari (Biomedical Journal of Indonesia, 2022)
Genetic is one of the most common causes of hearing loss with more than a hundred genes related to hearing loss have been identified. A genetic diagnosis can assist clinicians to keep away from unimportant and expensive clinical examinations, put up prognostic information, and assist in constructing medical therapy for patients. The development of gene therapy to improve hereditary hearing loss continues to grow these days, showing promising results. This literature review aims to review the genetic aspects of hearing loss, focusing on the gene therapy.